Influence of Microstructural Evolution on the Magnetically Group Dominance in Polycrystalline Y3Fe5O12 Multi-Samples - Rodziah Nazlan; Mansor Hashim; Idza Riati Ibrahim; Nor Hapishah Abdullah; Fadzidah Mohd Idris; Ismayadi Ismail; Wan Norailiana Wan Ab Rahman (Trans Tech publication, 2024)
Non-Indexed Publication